Diallyl dimethyl ammonium chloride (DADMAC) and acrylic acid (AAc) embedded nonwoven irradiated polyethylene fabric as efficient adsorbent to separate U(VI) from aqueous solution - Sultana, Shahnaz; Rahman, Nazia; Razzak, Md; Sardar, Md Nabul (Environmental Research and Technology, 2023)
Selective isolation of uranium (VI) from wastewater is now a subject of concern due to its damaging effect on living beings. In this study, the pre-irradiation technique was used to prepare grafted polymeric adsorbent by diallyl dimethyl ammonium chloride (DADMAC) and acrylic acid (AAc) onto nonwoven polyethylene fabric (PE) and the grafted adsorbent was applied for uranium (VI) adsorption from aqueous solution by batch method. After irradiation of the non-woven polyethylene fabrics with 50 kGy radiation dose, the grafting reaction was carried out at 80 ºC with a monomer solution consisting of 20 g DADMAC and 20 g AAc to 110 mL deionized water. The prepared adsorbent was characterized by Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), and Thermo-gravimetric Analysis (TGA). After treatment with NaOH solution, the adsorption study was analyzed by pH, initial metal ion concentrations, contact time, and temperature on the adsorption of U(VI). The highest graft yield was achieved at 598%. The maximum adsorption capacity achieved at 160 mg/g was found by treating with 0.1M NaOH for 4 minutes with an initial concentration of 1000 ppm, pH 3.3, and a contact time of 48 hours at room temperature (25 °C). Kinetic adsorption data fitted better with the pseudo-second-order equation and a good correlation of experimental data with the Langmuir isotherm model suggested monolayer adsorption. Langmuir equation showed that the maximum adsorption capacity for U(VI) was 333.333 mg/g. The study depicted good results on the desorption and reuse of the adsorbent.